Motivations for Adopting Proactive Environmental Management Accounting Practices: Evidence from South African Firms - Thomas Nyahuna; Mishelle Doorasamy (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
By examining environmental management accounting practices (EMAP) in South African companies, the study assists the company management to better understand their EMAP more broadly and establish effective EMAP to improve environmental management. This paper explores EMAP adopted by South African companies in Gauteng province and understands the motivation for applying the EMAP. Companies from different industrial sectors were used as the study sample. To accomplish the major aim of the study, 202 questionnaires were received as valid from the environmental managers, accountants and production managers. The study establishes that the companies are mostly using environmental management system, environmental reporting, waste management and water conservation activities as the key EMAP. This indicates that South African companies opt for EMAP with little cost involved and EMAP that does not require advanced systems in place. Also, financial gains were identified as the major motivation of EMAP adoption. This is followed by stakeholder pressure, marketing pressure and regulatory pressure. This paper will amplify literature on the EMAP adopted within industrial sectors and the motivation of adopting EMAP from an emerging market standpoint.